Maternal and neonatal outcome of births planned in alongside midwifery units: a cohort study from a tertiary center in Germany - Waltraut M. Merz; Laura Tascon-Padron; Marie-Therese Puth; Andrea Heep; Sophia L. Tietjen; Matthias Schmid; Ulrich Gembruch (BMC, 2020)
Abstract Background For healthy women entering birth after uneventful pregnancy, midwife-led models of care have the potential to reduce interventions and increase the vaginal birth rate. In Germany, 98.4% of women are giving birth in consultant-led obstetric units. Alongside midwifery units (AMU) have been established in 2003. We compared the outcome of women registered for planned birth in the AMU at our hospital with a matched group of low-risk women who gave birth in standard obstetric care during the same period of time. Methods We used a retrospective cohort study design. The study group consisted of all women admitted to labor ward who had registered for birth in AMU from 2010 to 2017. For the control group, low-risk women were selected; additionally, matching was performed for parity. Mode of birth was chosen as primary outcome parameter for the mother. For the neonate, a composite primary outcome (5-min Apgar < 7 or umbilical cord arterial pH < 7.10 or transfer to specialist neonatal care) was defined. Secondary outcomes included epidural anesthesia, duration of the second stage of labor, episiotomy, obstetric injury, and postpartum hemorrhage. Non-inferiority was assessed, and multiple logistic regression analysis was performed. Results Six hundred twelve women were admitted for labor in AMU, the control group consisted of 612 women giving birth in standard obstetric care. Women in the study group were on average older and had a higher body mass index (BMI); birthweight was on average 95 g higher. Non-inferiority could be established for the primary outcome parameters. Epidural anesthesia and episiotomy rates were lower, and the mean duration of the second stage of labor was shorter in the study group; second-degree perineal tears were less common, higher-order obstetric lacerations occurred more frequently. Overall, 50.3% of women were transferred to standard obstetric care. Regression analysis revealed effects of parity, age and birthweight on the chance of transfer. Conclusion Compared to births in our consultant-led obstetric unit, the outcome of births planned in the AMU was not inferior, and intervention rates were lower. Our results support the integration of AMU as a complementary model of care for low-risk women.